Personality and Work Motivation: International Evidence - Dr. Vijay Gotham; Dr. Ramesh Kumar (Al-Qanṭara, 2022)
Abstract In an effort to increase normative commitment, principals should be supported by personality and work motivation. A number of research were lack of examining specifically normative commitment in educational organizations. Therefore, the purpose of this present study is to examine the direct influence of personality and work motivation on the normative commitment of the principals. The survey method with the path analysis approach was employed in this study. Based on the results of data analysis, it was concluded that personality and work motivation have a direct positive effect on the normative commitment of the principals, which means that better personality and higher work motivation will lead to the improvement of principals’ normative commitment.